ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (Studi Kasus Pada Badan Pendapatan Daerah Kota Batu tahun 2018-2020) - Linggam Wardani Putri; Afifudin Afifudin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to analyze the effectiveness of hotel taxes on increasing Regional Original Income and analyzing the contribution of hotel taxes to increasing Regional Original Income. The subjects in this study were hotels located in Batu City. This research uses quantitative methods. The results of this study indicate that the effectiveness of Batu City's hotel tax revenue in 2018-2020 is very effective, each percentage reaching the category of more than 100%. Meanwhile, the contribution of hotel taxes to Batu City's Original Revenue in 2018-2020 shows the criteria for being lacking.Keywords: Effectiveness, Contribution, Hotel Tax, Local Revenue